2009
DOI: 10.1590/s1413-70542009000100045
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade física e fisiológica de sementes de braquiárias comercializadas em Campo Grande-MS

Abstract: RESUMOConduziu-se, o presente trabalho, no Laboratório Didático de Análise de Sementes da Universidade para o Desenvolvimento do Estado e da Região do Pantanal -UNIDERP, com o objetivo de avaliar a qualidade física e fisiológica de sementes de três espécies de braquiárias (Brachiaria brizantha, B. humidicola e B. decumbens), provenientes de seis empresas estabelecidas no comércio de Campo Grande-MS. Os experimentos foram conduzidos em um delineamento inteiramente casualizado, em esquema fatorial 3 X 6, com trê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
1
6
0
10
Order By: Relevance
“…Similarly, the germination test, even though it is not a seed vigor test, maintained the decreasing order of classification of lots in terms of physiological potential, from lot 1 to 9; nevertheless, the germination test was more accurate than the previous test because it separated the seed lots into four classes of: high (1, 2 and 3), medium-high (4 and 5), medium-low (6) and low (7, 8 and 9) physiological potential. Other studies reported results similar to the findings of the present study, regarding the efficiency of the germination test in differentiating commercial lots of B. brizantha seeds (LAURA et al, 2009;OHLSON et al, 2011).…”
Section: Continuationsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the germination test, even though it is not a seed vigor test, maintained the decreasing order of classification of lots in terms of physiological potential, from lot 1 to 9; nevertheless, the germination test was more accurate than the previous test because it separated the seed lots into four classes of: high (1, 2 and 3), medium-high (4 and 5), medium-low (6) and low (7, 8 and 9) physiological potential. Other studies reported results similar to the findings of the present study, regarding the efficiency of the germination test in differentiating commercial lots of B. brizantha seeds (LAURA et al, 2009;OHLSON et al, 2011).…”
Section: Continuationsupporting
confidence: 91%
“…Although studies on vigor tests for grass seeds, including sweet corn (COIMBRA et al, 2009), maize (GRZYBOWSKI et al, 2015 and millet (MACHADO et al, 2012) seeds, advocate that these tests allow differentiating seed lots with similar germination percentages, this premise is difficult to confirm in forage grasses because seed lots of these species have differences in germination larger than those assessed in large-crop seeds (LAURA et al, 2009;OHLSON et al, 2011).…”
Section: Continuationmentioning
confidence: 99%
“…Some studies on the quality of forage seeds have verified differences in the physical quality of lots. Laura et al (2009), in a study with U. brizantha, U. humidicola and U. decumbens seeds verified differences in the physical purity of six lots of each species in different locations in the region of Campo Grande -MS. However, in this work, the incidence of weed seeds was not evaluated.…”
Section: Introductionmentioning
confidence: 77%
“…High germination and rapid seedling development are prerequisites for successful pasture or sward establishment (SOUZA SOBRIHNO et. al., 2008;LAURA et. al., 2009;KOJOROSKI-SILVA et.…”
Section: Resultsmentioning
confidence: 99%